Exploring the Dynamics of GDP Growth and Unemployment Rates in Asian Economies: A Longitudinal Analysis - Ang, Syh Han (Journal of Business and Economic Options, 2022)
This study represents a significant contribution to our understanding of the relationship between GDP growth and unemployment rates in both developed and developing Asian countries. By applying the Okun's law framework and utilizing advanced econometric techniques such as co-integration analysis and Granger-causality testing, the study offers valuable insights into the dynamics of this relationship over a period spanning more than four decades. The findings reveal that both developed and developing Asian countries exhibit a negative relationship between GDP growth and unemployment rates, consistent with the theoretical underpinnings of Okun's law. However, the study goes beyond traditional Okun's law analysis by estimating long-run and short-run coefficients using the ARDL approach. Remarkably, the coefficients obtained for some developed and developing Asian countries are higher than those predicted by the original Okun's law, suggesting a robustness of the relationship in these contexts. This nuanced understanding of the relationship between GDP growth and unemployment rates in Asian economies underscores the importance of considering regional and developmental factors when analyzing macroeconomic phenomena. The findings of this study have implications for policymakers and practitioners seeking to address unemployment challenges and promote sustainable economic growth in the region. Furthermore, by identifying deviations from traditional Okun's law predictions, this study contributes to the refinement of economic models and frameworks tailored to the specific characteristics of Asian economies. This highlights the need for ongoing research and analysis to better understand the drivers of economic performance and inform evidence-based policy formulation. Overall, this study enriches our knowledge of the macroeconomic dynamics in Asian countries and provides a valuable foundation for future research on the relationship between GDP growth and unemployment rates in both developed and developing contexts.